Propagation of Spermatogonial Stem Cell-Like Cells From Infant Boys - Dong, Lihua; Kristensen, Stine Gry; Hildorf, Simone; Gul, Murat; Clasen-Linde, Erik; Fedder, Jens; Hoffmann, Eva R.; Cortes, Dina; Thorup, Jorgen; Andersen, Claus Yding (Frontiers in Physiology, 2019)
Background: Gonadotoxic treatment of malignant diseases as well as some non-malignant diseases such as cryptorchidism in young boys may result in infertility and failure to father children later in life. As a fertility preserving strategy, several health centers collect testicular biopsies to cryopreserve spermatogonial stem cells (SSCs) world-wide. One of the most promising therapeutic strategies is to transplant SSCs back into the seminiferous tubules to initiate endogenous spermatogenesis. However, to obtain sufficient numbers of SSC to warrant transplantation, in vitro propagation of cells is needed together with proper validation of their stem cell identity. Materials and methods: Minute amounts of testicular biopsies (5-10 mg) were processed by mechanical and enzymatic digestion. SSCs were enriched by differential plating method in StemPro-34 medium supplemented with several growth factors. SSC-like cell clusters (SSCLCs) were passaged 5 times. SSCLCs were identified by immunohistochemical and immunofluorescence staining, using protein expression patterns in testis biopsies as reference. Quantitative polymerase chain reaction analysis of SSC markers LIN-28 homolog A (LIN28A), G antigen 1 (GAGE1), promyelocytic leukemia zinc finger protein (PLZF), integrin alpha 6 (ITGA6), ubiquitin carboxy-terminal hydrolase L1 (UCHL1) and integrin beta 1 (ITGB1) were also used to validate the SSC-like cell identity. Results: Proliferation of SSCs was achieved as formation of SSCLCs was consistently observed during 5 passages. The presence of SSCs in SSCLCs was confirmed by positive immunostaining of LIN28, UCHL1 and PLZF and quantitative polymerase chain reaction for LIN28A, UCHL1, PLZF, ITGA6 and ITGB1, respectively. Conclusions: This study has demonstrated that SSCs from infant boys potentially possess the capacity for in vitro proliferation and advance a fertility preservation strategy for young boys, who adversely may lose their fertility.